EDUKASI DAN SOSIALISASI GERAKAN MASYARAKAT CERDAS MENGGUNAKAN DAN MENGENAL OBAT - Ratna Mildawati; Neta Ayu Andera; Lailaturohmah (Jurnal LENTERA, 2023)
Drugs are materials or guide materials, including biological products that are used to influence or investigate physiological systems or pathological conditions in the context of establishing a diagnosis, prevention, cure, recovery, health promotion and contraception, for humans. Currently, drugs and food are still circulating that do not meet the requirements of the Food and Drug Monitoring Agency (BPOM). In order to use drugs correctly, the public needs clear, correct and reliable information, so that the determination of the type and amount of drugs needed must be based on rational use. . This service method begins with situation analysis, problem identification, and problem prioritization. The design of the intervention activity is in the form of an explanation of material related to knowing the proper and correct use of drugs and in order to create awareness, awareness, understanding and increase public knowledge in using drugs properly and correctly intervention using a questionnaire. The service was carried out directly or face to face to 30 participants in Gampengrejo Village. The result of education and socialization is the improvement of societal values in understanding the correct and proper use of medication. Prior to education, the percentage of respondents with good knowledge was 30%, whereas after receiving education, it increased to 90% in the good category, resulting in a 60% improvement. Drugs are an important component that cannot be replaced in health services.